Preemptive Infiltration of Local Anesthetics During Vaginal Hysterectomy: A Systematic Review and Meta-analysis of Randomized Controlled Trials. Issue 10 (27th October 2022) - Zacharakis, Dimitrios; Prodromidou, Anastasia; Douligeris, Athanasios; Athanasiou, Stavros; Hadzilia, Sophia; Kathopoulis, Nikolaos; Athanasiou, Veatriki; Grigoriadis, Themos
Abstract : Importance: Vaginal hysterectomy (VH) is the preferred route of choice for women desiring hysterectomy to treat uterine pathology, including premalignant conditions and fibroids. Objective: The aim of this study was to evaluate the impact of the use of preemptive local analgesia (LA) on postoperative pain and perioperative outcomes for women undergoing VH. Study Design: A systematic search of 4 electronic databases (MEDLINE, Scopus, Cochrane CENTRAL Register of Controlled Trials, and Clinicaltrials.gov ) was performed for articles published up to January 2021. All randomized controlled trials that presented outcomes of patients who underwent VH due to pelvic floor disorders or other benign gynecological disorders and received local infiltration analgesia were finally included. Results: A total of 5 studies with 277 women (138 LA group vs 199 no-LA group) who underwent a VH were included in the present meta-analysis. Mean pain scores at both 30 minutes to 2 hours and 3 to 6 hours postoperatively were significantly lower in the LA group compared with the non-LA group (220 patients: mean difference [MD], −1.75; 95% confidence interval [CI], −2.77 to −0.74; P = 0.0007; and 220 patients: MD, −1.68; 95% CI, −2.28 to 1.09; P < 0.00001, respectively). Morphine/narcotic opioid-based consumption up to 24 hours postoperatively was significantly reduced in the LA group compared with the non-LA group (197 patients MD, −9.47 mg; 95% CI, −16.51 to −2.43; P = 0.008). Conclusions: The use of preemptive LA during VH seems to be beneficial especially with regard to short-term postoperative pain and opioid use. However, further studies are needed to identify the optimal anesthetic regimen, the dosage, and sites of application aiming to achieve the optimal benefit in the postoperative management.